The complete guide to walls & ceilings : framing, drywall, painting, trimwork. (Cool Springs Press, 2015)
Confidently tackle--and accomplish--any wall or ceiling project yourself, with our help! Wallsand ceilings are vital to the structural integrity and the overall appearance of any home, so they are worth your time and care. Black & Decker The Complete Guide to Walls & Ceilings gives you all the information you need to understand and maintain structural integrity, while reimagining and remodeling visible surfaces to meet your home decor needs. When you decide to remove a wall and open up the space or create a new wall and a new room, you'll see for yourself how great the impact of walls and ceilings is. All the essentials of framing walls and ceilings are shown with beautiful step-by-step photos in exhaustive detail, including framing window and door openings. You'll also learn the tips and techniques for hanging and finishing drywall on horizontal and vertical surfaces. If you've ever taped and mudded drywall in the past, you'll be amazed to see how much less labor and mess it involves when it's done the correct way. Choosing and applying wallcoverings is also covered in this new book from the experts at BLACK+DECKER, as is the final step in your wall or ceiling project: installing trimwork. Baseboard, crown molding, door and window trim, and much more are explained with color photos and easy-to-follow instructions.